A revision of the planthopper genus Chionomus Fennah (Hemiptera: Fulgoroidea: Delphacidae) - Weglarz, Kathryn M.; Bartlett, Charles R (Zootaxa, 2020)
The planthopper genus Chionomus Fennah, 1971 (Hemiptera: Fulgoroidea: Delphacidae) currently includes three Neotropical species, removed from the polyphyletic genus Delphacodes Fieber, 1866. Morphological and molecular evidence further redefine Chionomus to include ten additional species (eight species removed from Delphacodes, two described as new, viz. Chionomus dolonus n. sp. and C. herkos n. sp.), with another four species synonymized. Phylogenetic analyses of morphological and molecular sequence data of the mitochondrial gene Cytochrome Oxidase I provide support for the monophyly of Chionomus. We use a mixed model Bayesian optimality criterion to define phylogenetic relationships among Chionomus and support paraphyly of the original definition of Chionomus (with respect to Delphacodes) and monophyly of the revised genus.